High frequency of point mutations in the nitroreductase 4 and 6 genes of Trichomonas vaginalis associated with metronidazole resistance - Iturrieta-Gonzalez, Isabel; Olivares-Ferretti, Pamela; Hidalgo, Alejandro; Zambrano, Fabiola; Ossa, Ximena; Fonseca-Salamanca, Flery; Melo, Angelica (Folia parasitologica, 2024)
Trichomoniasis, a globally distributed sexually transmitted infection, is caused by the urogenital parasite Trichomonas vaginalis Donné, 1836 affecting both women and men. The treatment of choice is metronidazole (MTZ). In the present study, 15 samples of vaginal discharge and urine were analysed by sequencing nitroreductase genes (ntr4 and ntr6). An in silico model was structured to illustrate the location of point mutations (PM) in the protein. The ntr4 gene presented four PMs: G76C (10/10), C213G (9/10), C318A (5/10) and G424A (1/10), while the ntr6 gene had eight PMs; G593A (13/13) the most frequent, G72T and G627C, both in 8/13. The PM C213G and A438T generated a stop codon causing a truncated nitroreductase 4 and 6 protein. Docking analysis demonstrated that some models had a decrease in binding affinity to MTZ (p < 0.0001). A high frequency of mutations was observed in the samples analysed that could be associated with resistance to MTZ in Chile.
Keywords: bodová mutace; genital infection; Trichomonas Vaginitis; trichomoniasis; clinical samples.; léková rezistence; lidé; protozoální proteiny; Nitroreductases; Humans; Protozoan Proteins; Chile; protein polymorphism; trichomonádová vaginitida; Drug Resistance; Point Mutation; nitroreduktasy; Metronidazole; dysfunctional enzyme; refractory treatment; ženské pohlaví; Antiprotozoal Agents; antiprotozoální látky; Female; Trichomonas vaginalis; metronidazol